ANALISIS PERBEDAAN TAFSIR MENGENAI PERSESUAIAN ALAT BUKTI DALAM PEMBUKTIAN TINDAK PIDANA PENIPUAN (STUDI PUTUSAN NOMOR: 278/PID.B/2021/PN.TNG): Analysis Of The Differences In Interpretation Regarding The Suitability Of Evidence In The Proof Of Fraud Offenses (Study Of Verdict Number: 278/Pid.B/2021/Pn.Tng) - Bobby Firmansyah; Setiyono (Faculty of Law, Universitas Trisakti, 2025)
Based on the applicable legislation, the Defendant Timothy Tandiokusuma should have been sentenced for the crime of fraud and deceit. The identification of the problem in this research is how the conformity of evidence proves the existence of fraud (Case Study Number: 278/Pid.B/2021/PN.Tng) and how the legal considerations of the Tangerang District Court judge in acquitting Timothy Tandiokusuma (Case Study Number: 278/Pid.B/2021/PN.Tng). The conformity of evidence has met the principles of Article 185 paragraph (6) of the Criminal Code, which is the method used by a judge in sentencing the Defendant. Data analysis was conducted descriptively and conclusions were drawn using deductive methods. Based on the research results and conclusions, it is concluded that there was an error by the Panel of Judges in sentencing the defendant due to not paying attention to the conformity of the evidence. In this case, the Panel of Judges only referred to evidence such as witness statements, bank statements, checks, and contract letters, and considered the act as not a criminal offense but rather a civil matter. The victim witness who suffered losses due to the Defendant's actions should have filed a fraud claim to obtain compensation.